2002
DOI: 10.1002/1099-0690(200205)2002:10<1603::aid-ejoc1603>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromics by Intramolecular Redox Switching of Single Bonds

Abstract: Compounds of the general structure presented in Scheme 1 are proposed as electrochromic systems (ESs) in which reversible electron transfer is associated with breaking or forming of single bonds. In contrast to classical ESs, both redox states represent closed-shell systems. Whereas type OL/CS (Open form − Long-wavelength absorption/Closed form − Short-wavelength absorption) has already been demonstrated, this paper presents examples of the OS/CL type, in which the long-wavelength absorption is displayed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…They are promising candidates for use as chiral redox memories . Compared with extensive studies on electrochromic materials that give UV−vis spectral changes as a sole output, there have been only a few successful examples reported so far of those involving changes in CD spectra. , During the course of our continuing study on new electrochromic materials, we found that β,β-bis(4-dimethylaminophenyl)styrene ( 5 ) undergoes oxidative dimerization to give a stable salt of 1,4-dication 6 2+ in quantitative yield 2c (Scheme ). This result prompted us to design novel bichromophoric redox pairs containing a biaryl skeleton, where the oxidative C−C bonding to the dication is an intramolecular process.…”
mentioning
confidence: 97%
“…They are promising candidates for use as chiral redox memories . Compared with extensive studies on electrochromic materials that give UV−vis spectral changes as a sole output, there have been only a few successful examples reported so far of those involving changes in CD spectra. , During the course of our continuing study on new electrochromic materials, we found that β,β-bis(4-dimethylaminophenyl)styrene ( 5 ) undergoes oxidative dimerization to give a stable salt of 1,4-dication 6 2+ in quantitative yield 2c (Scheme ). This result prompted us to design novel bichromophoric redox pairs containing a biaryl skeleton, where the oxidative C−C bonding to the dication is an intramolecular process.…”
mentioning
confidence: 97%